Review on recent progress in synthesis, properties, and applications of MXenes - Borah, Ashish Jyoti; Natu, Varun; Biswas, Abhijit; Srivastava, Anchal (Oxford Open Materials Science, 2025)
<h2 class="abstract-title js-splitscreen-abstract-title" id="540140110" scrollto-destination="540140110" style="box-sizing: border-box; margin-top: 0px; margin-right: 0px; margin-left: 0px; padding: 1.5rem 1.2rem 0.9rem; border: 0px; font-variant-numeric: inherit; font-variant-east-asian: inherit; font-variant-alternates: inherit; font-variant-position: inherit; font-variant-emoji: inherit; font-stretch: inherit; font-size: 1.25rem; line-height: 1em; font-family: "Source Sans Pro", Helvetica, Arial, sans-serif; font-optical-sizing: inherit; font-size-adjust: inherit; font-kerning: inherit; font-feature-settings: inherit; font-variation-settings: inherit; font-language-override: inherit; vertical-align: baseline; background: rgb(239, 242, 247); color: rgb(42, 42, 42); margin-bottom: 0px !important;"> Abstract <section aria-label="Main abstract" class="abstract" style="box-sizing: border-box; margin: 0px; padding: 0px 1.2rem 1.7rem; border: 0px; font-variant-numeric: inherit; font-variant-east-asian: inherit; font-variant-alternates: inherit; font-variant-position: inherit; font-variant-emoji: inherit; font-stretch: inherit; font-size: medium; line-height: inherit; font-family: Merriweather, serif; font-optical-sizing: inherit; font-size-adjust: inherit; font-kerning: inherit; font-feature-settings: inherit; font-variation-settings: inherit; font-language-override: inherit; vertical-align: baseline; position: relative; background: rgb(239, 242, 247); color: rgb(42, 42, 42);"> <p class="chapter-para" style="box-sizing: border-box; margin: 0px; padding: 0px; border: 0px; font-style: inherit; font-variant: inherit; font-weight: inherit; font-stretch: inherit; font-size: 15px; line-height: 1.7em; font-family: inherit; font-optical-sizing: inherit; font-size-adjust: inherit; font-kerning: inherit; font-feature-settings: inherit; font-variation-settings: inherit; font-language-override: inherit; vertical-align: baseline;"> MXenes, a noble class of two-dimensional (2D) material, discovered in 2011 have gained attention in recent years. They have attracted significant attention due to their flexible elemental composition, distinctive 2D-layered architecture, large surface area, and abundant surface terminations. Top-down synthesis techniques such as HF etching, alkaline etching, and electrochemical methods are used for MXene synthesis. Alongside these methods, methods like chemical vapor deposition (CVD), template method and plasma enhanced pulsed layer deposition (PELPD) are also used for the thin-film synthesis of MXenes. The discovery of double transition-metal layered MXene, solid, and high entropy MXene open up the prospect of further novel structures. MXenes are electrically conductive and have promising optoelectronic, mechanical, and thermoelectric properties. MXenes have also shown immense potential in biomedicine and environmental applications. The surface chemistry of MXene make them ideal for biosensors, drug delivery, and photothermal therapy, while their photocatalytic and adsorption properties enable efficient removal of pollutants and contaminants from water. This review examines the various MAX phase synthesis methods, such as solid-state reactions, hot isostatic pressing, and spark plasma sintering, followed by top-down techniques like HF etching, alkaline etching, and electrochemical etching, as well as bottom-up methods like CVD, template approaches, and plasma-enhanced pulsed layer deposition. The review also looks into the optical, chemical, and electronic properties of MXene, as well as their advancements in energy storage, optoelectronics, pollution avoidance, biomedical applications, and more.